Integrating artificial intelligence into veterinary education: student perspectives - de Brito, Christelle; Redondo, José I.; Tadeo-Cervera, Irene; Bataller, Esther; García-Roselló, Mireia; Cuquerella Madoz, Inmaculada; Terrado, José (Frontiers in Veterinary Science, 2025)
IntroductionAdvancements in technology have fostered a continuous evolution of higher education, driving the adoption of innovative tools, including artificial intelligence (AI). This study explores veterinary students’ interest in AI, their training and experiences, and their perceptions on AI integration in veterinary medicine.MethodsA comprehensive survey was administered to veterinary students at the Faculty of Veterinary Medicine of a single international university in Spain, focusing on their experience with AI, their perception of its integration into veterinary education, and their views on its future role in veterinary medicine.ResultsSix hundred and four students of 34 nationalities across all academic years answered the survey. Most students were familiar with AI tools and primarily utilize them in academic settings, recognizing AI as a valuable educational resource. The majority believed universities should encourage and regulate AI use. There was a strong desire to integrate AI-related education into the veterinary curriculum, with students eager to learn more about specific AI applications in various veterinary fields, in particular clinical patient monitoring and veterinary management. The study also highlights the need for training in AI principles and regulation. Likewise, students expressed concerns about ethical and responsible use of AI, as well as the reliability of AI responses.DiscussionThis study underscores the importance of integrating AI training in veterinary education to enhance students’ competencies. By providing targeted training and support, universities can help students harness the potential of AI while ensuring its ethical and effective use in their careers. This research emphasizes the need for continuous curriculum adaptation to keep pace with technological advancements and meet the evolving demands of veterinary medicine education.